Convenient and versatile DNA extraction using agarose plugs for ribotyping of problematic bacterial species. - Nair, S.; Karim, R.; Cardosa, Mary Jane; Ismail, G.; Pang, T. (Elsevier, 1999)
We describe a convenient, versatile and safe method for preparing bacterial DNA for ribotyping analysis. In this method, extraction of bacterial DNA from Salmnonella typhi and Burkholderia pseudomallei. and subsequent restriction endonuclease digestion, was performed in agarose blocks/plugs thus minimizing shearing and loss of DNA, problems commonly associated with liquid phase phenol extraction. Digested DNA in the plugs was then electrophoresed directly, transferred to nylon membranes and hybridized with labeled rDNA probes in the usual manner to provide reproducible restriction patterns. This method is particularly useful for bacterial species where standard DNA extraction in the liquid phase using phenol has been problematic (e.g. B. pseudomallei) but can be used for any bacterial species. The DNA extracted within the agarose plugs can be stored for long periods and can be used in other, widely-used typing methods such as pulsed-field gel electrophoresis (PFGE) and PCR-based techniques. Embedding live cells directly in agarose plugs also minimizes the risk of exposure to these virulent human pathogens among laboratory workers.